2011
DOI: 10.1016/j.vetmic.2010.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Moraxella species that causes epistaxis in macaques

Abstract: Bacteria of the genus Moraxella have been isolated from a variety of mammalian hosts. In a prior survey of bacteria that colonize the rhesus macaque nasopharynx, performed at the Tulane National Primate Research Center, organisms of the Moraxella genus were isolated from animals with epistaxis, or “bloody nose syndrome.” They were biochemically identified as Moraxella catarrhalis, and cryopreserved. Another isolate was obtained from an epistatic cynomolgus macaque at the U.S. Army Medical Research Institute of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 19 publications
(27 reference statements)
0
25
0
Order By: Relevance
“…Clinical signs occur most commonly in dry winter months and may also include sneezing and occasionally, periorbital swelling. Sequencing of the 16S ribosomal RNA gene indicated that isolates from macaques were most closely related to M. lincolnii and rhesus macaques were resistant to infection with human strains of M. catarrhalis (Embers et al, 2011). Treatment with long-acting penicillin may be effective (VandeWoude and Luzarraga, 1991), but recurrent infections are possible if low-humidity conditions persist.…”
Section: F Moraxella Catarrhalismentioning
confidence: 99%
“…Clinical signs occur most commonly in dry winter months and may also include sneezing and occasionally, periorbital swelling. Sequencing of the 16S ribosomal RNA gene indicated that isolates from macaques were most closely related to M. lincolnii and rhesus macaques were resistant to infection with human strains of M. catarrhalis (Embers et al, 2011). Treatment with long-acting penicillin may be effective (VandeWoude and Luzarraga, 1991), but recurrent infections are possible if low-humidity conditions persist.…”
Section: F Moraxella Catarrhalismentioning
confidence: 99%
“…Previous outbreaks of epistaxis among cynomolgus macaques have been attributed to Branhamella ( Moraxella ) catarrhalis (3) or Neisseria ( Moraxella ) catarrhalis (4) based on biochemical testing. While the results of phenotypic and biochemical testing of M. macacae were consistent with those of M. catarrhalis , sequence analysis of the 16S rRNA indicated only 88% identity to M. catarrhalis (2). In fact, the closest 16S sequence match was to M. lincolnii , a human respiratory tract inhabitant, with 90% nucleotide identity (2).…”
Section: Genome Announcementmentioning
confidence: 76%
“…The most important human-pathogenic species is M. catarrhalis , a major cause of upper and lower respiratory tract infections, sinusitis, and childhood otitis media (1). Moraxella macacae is a recently described species causing epistaxis, or bloody nose syndrome, in both rhesus macaques from the Tulane National Primate Research Center and cynomolgus macaques from the U.S. Army Medical Research Institute of Infectious Diseases (USAMRIID) (2). Previous outbreaks of epistaxis among cynomolgus macaques have been attributed to Branhamella ( Moraxella ) catarrhalis (3) or Neisseria ( Moraxella ) catarrhalis (4) based on biochemical testing.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Detection of M. macacae thus far has been based on traditional microbiological and biochemical methods. Unfortunately, with the exception of beta‐lactamase, M. macacae exhibits identical reactivity in the biochemical tests of the API NH panel (BioMérieux, Durham, NC, USA) as M. catarrhalis , the human pathogenic species . In fact, previous descriptions of bloody nose syndrome in non‐human primates in 1991 and 2002 were attributed to M .…”
Section: Introductionmentioning
confidence: 99%
“…( Branhamella ) catarrhalis based on colony morphology, Gram stain, and biochemical analysis, but were most likely due to M. macacae . Proper identification of M. macacae was ultimately only made by sequence analysis of its 16S rRNA gene .…”
Section: Introductionmentioning
confidence: 99%